2020
DOI: 10.3390/su12219002
|View full text |Cite
|
Sign up to set email alerts
|

Soil Contamination in Areas Impacted by Military Activities: A Critical Review

Abstract: Military activities drastically affect soil properties mainly via physical/chemical disturbances during military training and warfare. The present paper aims to review (1) physical/chemical disturbances in soils following military activities, (2) approaches to characterization of contaminated military-impacted sites, and (3) advances in human health risk assessment for evaluating potential adverse impacts. A literature search mainly covering the period 2010–2020 but also including relevant selected papers publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 135 publications
(298 reference statements)
0
20
0
9
Order By: Relevance
“…EF provides accurate assessment of heavy metals accumulation from anthropogenic sources [25,26] which was why it was carried out in this study. [22] which indicated that military activities did impact on the areas of activities zones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EF provides accurate assessment of heavy metals accumulation from anthropogenic sources [25,26] which was why it was carried out in this study. [22] which indicated that military activities did impact on the areas of activities zones.…”
Section: Resultsmentioning
confidence: 99%
“…The study demonstrated that Cd and Hg had higher levels of ecological risk for agricultural soil in Shanxi Province of China. Broomandi et al [22] worked on critical review of soil contamination in areas impacted by military activities. The work showed that heavy metals have been found in elevated concentrations in many military impacted zones.…”
Section: Introductionmentioning
confidence: 99%
“…However, the article considers only one side of the problemthe assessment of the explosives effect on humans (children and adults) with only one route of exposureoral. The lack of data about the location of explosive objects in the soil of Donbas does not allow us fully assess their toxicological hazard to humans and the environment, although the literature indicates the dangerous effects of explosives (Pichtel, 2012, Broomandi et al, 2020. The problem of the toxicological impact of explosive residues on residents and the environment of Donbas remains relevant.…”
Section: Discussionmentioning
confidence: 99%
“…They are consumed by animals and humans and cause harm to them. As a result, war zones with intense conflicts, military training areas, shooting sports zones, explosives and ammunition manufacturing/disposal locations are considered among the major sources of contamination for terrestrial ecosystems (Broomandi et al 2020;Ryu, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Octane and heptane were used as nonpolar probe compounds. Dimethyl methylphosphonate (DMMP), which can be an environmental contaminant and has a representative structure of organophosphorus compounds (e.g., pesticides), was used as a polar probe compound. Note, in this paper, we use the word vapor to refer to a gas from a probe compound that is generally a liquid under ambient conditions.…”
Section: Materials and Methodsmentioning
confidence: 99%